Herzberg-Teller Effect on the Vibrationally Resolved Absorption Spectra of Single-Crystalline Pentacene at Finite Temperatures - Qian, Yuqin; Li, Xia; Harutyunyan, Avetik R; Chen, Gugang; Rao, Yi; Chen, Hanning (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2020)
The line shape of an electronic spectrum conveys the coupling between electronic and vibrational degrees of freedom. In the present study, the light absorption spectra of single-crystalline pentacene were measured by polarized UV-vis microscopy at 77, 185, and 293 K. The vibronic coupling encoded in each spectrum was resolved by the Herzberg-Teller theory that considers the contributions from the Franck-Condon (FC) factor, Franck-Condo/Herzberg-Teller (FC/HT) interference, and Herzberg-Teller (HT) coupling. Specifically, excitation energies, electronic transition dipole moments, and their nuclear gradients were evaluated by the GW method to ensure numerical accuracy, while the computationally efficient density function theory was employed to determine the optimized structures and vibrational normal modes. For every pair of electronic transition and normal mode that gives rise to a strong vibronic transition intensity, we examined their spatial characteristics by projecting them onto the three crystal axes. It was found that all normal modes strongly coupled to the lowest-lying a-polarized electronic transitions oscillate along axis a, whereas none of their counterparts for the lowest-lying b-polarized electronic transitions is predominantly along axis b. This notable difference on the alignment between the electronic transition and molecular vibration could help the directional control of charge dissociation and/or spin separation. Moreover, a significant variance of the destructive FC/HT interference was discovered with increasing temperatures that can well explain the a-polarized fading tableland near 650 nm. Finally, the importance of HT coupling was corroborated by comparing its intensity with those of FC factor and FC/HT interference. Taken all together, the vibrational dependence of the electronic wave function is critical to resolve the light absorption spectra of single-crystalline pentacene and its temperature effects, facilitating the systematic design of functional optical materials based on pentacene and its derivatives.The line shape of an electronic spectrum conveys the coupling between electronic and vibrational degrees of freedom. In the present study, the light absorption spectra of single-crystalline pentacene were measured by polarized UV-vis microscopy at 77, 185, and 293 K. The vibronic coupling encoded in each spectrum was resolved by the Herzberg-Teller theory that considers the contributions from the Franck-Condon (FC) factor, Franck-Condo/Herzberg-Teller (FC/HT) interference, and Herzberg-Teller (HT) coupling. Specifically, excitation energies, electronic transition dipole moments, and their nuclear gradients were evaluated by the GW method to ensure numerical accuracy, while the computationally efficient density function theory was employed to determine the optimized structures and vibrational normal modes. For every pair of electronic transition and normal mode that gives rise to a strong vibronic transition intensity, we examined their spatial characteristics by projecting them onto the three crystal axes. It was found that all normal modes strongly coupled to the lowest-lying a-polarized electronic transitions oscillate along axis a, whereas none of their counterparts for the lowest-lying b-polarized electronic transitions is predominantly along axis b. This notable difference on the alignment between the electronic transition and molecular vibration could help the directional control of charge dissociation and/or spin separation. Moreover, a significant variance of the destructive FC/HT interference was discovered with increasing temperatures that can well explain the a-polarized fading tableland near 650 nm. Finally, the importance of HT coupling was corroborated by comparing its intensity with those of FC factor and FC/HT interference. Taken all together, the vibrational dependence of the electronic wave function is critical to resolve the light absorption spectra of single-crystalline pentacene and its temperature effects, facilitating the systematic design of functional optical materials based on pentacene and its derivatives.